2019
DOI: 10.1038/s41467-019-12314-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfect proton selectivity in ion transport through two-dimensional crystals

Abstract: Defect-free monolayers of graphene and hexagonal boron nitride are surprisingly permeable to thermal protons, despite being completely impenetrable to all gases. It remains untested whether small ions can permeate through the two-dimensional crystals. Here we show that mechanically exfoliated graphene and hexagonal boron nitride exhibit perfect Nernst selectivity such that only protons can permeate through, with no detectable flow of counterions. In the experiments, we use suspended monolayers that have few, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 25 publications
6
82
0
Order By: Relevance
“…For Raman spectroscopy, a typical quality control experiment, the detectable concentration limit of topological SW 55–77 defects in a graphene monolayer is about 2 × 10 9 cm −2 , [ 26–28 ] well above the ppm‐scale concentration of 7MR that is needed to govern the proton transfer. At the same time, our conclusions are in agreement with a recent experiment by Lozada‐Hidalgo and co‐workers, [ 15 ] which showed that the membranes employed in earlier experiments are free of vacancy defects. Vacancy defects and their energy barriers have been discussed in the literature by others.…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…For Raman spectroscopy, a typical quality control experiment, the detectable concentration limit of topological SW 55–77 defects in a graphene monolayer is about 2 × 10 9 cm −2 , [ 26–28 ] well above the ppm‐scale concentration of 7MR that is needed to govern the proton transfer. At the same time, our conclusions are in agreement with a recent experiment by Lozada‐Hidalgo and co‐workers, [ 15 ] which showed that the membranes employed in earlier experiments are free of vacancy defects. Vacancy defects and their energy barriers have been discussed in the literature by others.…”
Section: Figuresupporting
confidence: 93%
“…The underlying question is whether or not thermal protons can permeate through perfect 2D membranes. While the original experiments by Lozada‐Hidalgo, Geim, and co‐workers report high permeability and isotope selectivity in the 2D defect‐free materials, [ 6,7,15 ] other experimental works either report improved results using chemical vapor deposited (CVD) 2D systems [ 13 ] or suggest that the proton flow penetrates through local defects rather than the defect‐free graphene membrane. [ 10,14 ] Recent nanoballoon tests unambiguously showed that there are no atomic‐vacancy defects in the graphene used in the previous experiments.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…has greatly enriched and promoted the field of nanofluid ion transport [ 5 ]. Compared with nanopores or other nanofluidic channels, 2D nanofluidic channel systems with high flow rates are relatively easy and expandable to manufacture, which can be used for applications in bionic transmission and manipulation of ions, molecular screening, and energy conversion [ 6 , 7 , 8 ]. However, the currently reported research on the asymmetric ion transmission characteristics of the 2D nanofluidic homogeneous structure is still in its infancy, due to their problems of insufficient charge density and low rectification ratio [ 9 ].…”
Section: Introductionmentioning
confidence: 99%